2018
DOI: 10.1521/aeap.2018.30.6.490
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Exposure Prophylaxis (PrEP) Awareness and Acceptability Among Men Who Have Sex With Men in Taiwan

Abstract: Gay and other men who have sex with men (MSM) account for the vast majority of new HIV infections in Taiwan, yet utilization of pre-exposure prophylaxis (PrEP) remains low. We examined correlates of PrEP awareness and acceptability among MSM in Taiwan. A cross-sectional survey was conducted with 176 MSM (mean age = 27.4 years) recruited through community-based organizations in two cities. Less than half of participants (47.2%) were aware of PrEP; however, when it was described to them, the majority (72.2%) ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
7
1
Order By: Relevance
“…International evidence corroborates these findings and indicates that PrEP and PEP awareness is low, even among key populations that are considered a priority for infection control, the percentage of participants who had knowledge about either of the two methods ranges from 18.9 to 47.2% [14,29]. Besides, a study with MSM identified low awareness of the two methods but a high level of interest in using them [5].…”
Section: Discussionmentioning
confidence: 68%
“…International evidence corroborates these findings and indicates that PrEP and PEP awareness is low, even among key populations that are considered a priority for infection control, the percentage of participants who had knowledge about either of the two methods ranges from 18.9 to 47.2% [14,29]. Besides, a study with MSM identified low awareness of the two methods but a high level of interest in using them [5].…”
Section: Discussionmentioning
confidence: 68%
“…International evidence corroborates these ndings and indicates that awareness of PrEP and PEP is low, even among key populations that are considered a priority for infection control, the percentage of participants who had knowledge about either of the two methodsranges from 18.9-47.2% [16,23]. In addition, a study with MSM identi ed low awareness of the two methods, but a high level of interest in using them [3].…”
Section: Discussionmentioning
confidence: 65%
“…International evidence corroborates these ndings and indicates that PrEP and PEP awareness is low, even among key populations that are considered a priority for infection control, the percentage of participants who had knowledge about either of the two methods ranges from 18.9% to 47.2% [14,29]. Besides, a study with MSM identi ed low awareness of the two methods but a high level of interest in using them [5].…”
Section: Discussionmentioning
confidence: 67%